Dragon fruit farming by-products as an important source of several glycosylated flavonoids - Canute Kamikawachi, Renan [UNESP]; Carrara, Virginia [UNESP]; Vilegas, Wagner [UNESP] (Elsevier, 2023)
Plants are globally used as an alternative for conventional drugs in treatment of many diseases. A significant proportion of medicinal properties of plants is addressed to antioxidant constituents as flavonoids and phenolic acids. The genus Selenicereus, known as dragon fruit, has about 15 species of epiphytic or hemiepiphytic cactus with hotspots in the tropical region of Mexico. Recently, these plants have been the focus of pharmacological studies due to the antioxidant activity of its fruits. Although many studies have investigated the biological activities of fruits, few studies investigated the chemical constituents and biological activities of cladodes. Despite the little knowledge about cladodes, it has been already observed to have higher antioxidant activities and other biological activities than the fruits. Besides this, cladodes are by-products resulting from the year-round pruning. Another important point about studies involving dragon fruit is that none of them identify the variety that is being used. As it is a commercial plant, it has many varieties created by artificial selection and hybridization such as many other food plants. In this study we found that varieties from the same species showed quantitative and qualitative differences in the metabolite profile using LC-MS. Metabolite profile from Cerrado (Selenicereus setaceus) was closer to Branca (Selenicereus undatus) than Thick King (S. setaceus), as well as Golden (S. undatus) was closer to Thick King than Branca. These results show that it is essential to identify varieties that are being used in the studies, whereas studies that attempt to replicate the experiments or use these plants for phytopreparations are prone to mislead.